PELATIHAN PEMBELAJARAN CODING DALAM MERANCANG APLIKASI KALKULATOR SEDERHANA - Elnovreny, Jane; Sihotang , Siti Fatimah; Zuhri, Zuhri; Liwanda, Regina; Adellia, Juwita (Yayasan Education and Social Center, 2025)
A thorough understanding of stoichiometry is crucial for success in chemistry and related fields, such as biology, chemical engineering, and materials science. Without a solid understanding, students will struggle to interpret chemical equations, calculate the quantities of substances involved in reactions, and predict the outcome of reactions. However, learning stoichiometry often presents a challenge for students. Many students tend to be